Transistor- und Leitungsmodellierung zum Entwurf von monolithisch integrierten Leistungsverstärkern für den hohen Millimeterwellen-Frequenzbereich - Diebold, Sebastian (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2013)
The aim of this work is the design of monolithic integrated power amplifiers for frequencies from 200 to 250 GHz and beyond. For this, reliable and flexible transmission line and transistor models are required. The models are created and their accuracy is verified up to 325 GHz. An innovative coupler concept is developed. It is tailor-made for the applied MMIC-technology and the frequency range. Based on this coupler, a novel amplifier topology has been established and applied.